PENGARUH INFORMASI AKUNTANSI MANAJEMEN DAN PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA MANAJER PERHOTELAN - Pasla, Merry Christy; Ilat, Ventje; Pinatik, Sherly (GOING CONCERN : JURNAL RISET AKUNTANSI, 2013)
Survival and growth of a company depends on information systems used. One of information required by management is management accounting information. By using management accounting information for decision making, effectively decrease uncertaintly and reduce risk in choosing alternative. This research purpose to know how influential management accounting information and budget participation for hospitality manager performance especially in Manado. The type of data, that is data in quantitative by using likert scale obtained from hotel manager written response whom participating in budgeting. Research study with direct observation to the object. The results show management accounting information variables are influential to the hospitality manager performance and both of them have a positive relationship. This means that if that management accounting information are increases, then hospitality manager performance are also increases. Based on cateris paribus assumption, show that the impact of contribution or subscription from management accouting information and budget participation the fluctuations of manager performance in Manado.